2022
DOI: 10.3389/fpls.2022.910155
|View full text |Cite
|
Sign up to set email alerts
|

The Coordinated Action of MYB Activators and Repressors Controls Proanthocyanidin and Anthocyanin Biosynthesis in Vaccinium

Abstract: Vaccinium berries are regarded as “superfoods” owing to their high concentrations of anthocyanins, flavonoid metabolites that provide pigmentation and positively affect human health. Anthocyanin localization differs between the fruit of cultivated highbush blueberry (V. corymbosum) and wild bilberry (V. myrtillus), with the latter having deep red flesh coloration. Analysis of comparative transcriptomics across a developmental series of blueberry and bilberry fruit skin and flesh identified candidate anthocyani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…In our assay, co-infiltration with low amounts of VcMYBA1 was required to initiate anthocyanin production. VcMYBA1 has previously been found to control the activation of anthocyanin structural genes, such as DFR , ANS and UFGT ( Plunkett et al., 2018 ; Lafferty et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our assay, co-infiltration with low amounts of VcMYBA1 was required to initiate anthocyanin production. VcMYBA1 has previously been found to control the activation of anthocyanin structural genes, such as DFR , ANS and UFGT ( Plunkett et al., 2018 ; Lafferty et al., 2022a ).…”
Section: Discussionmentioning
confidence: 99%
“…The ANS phylogeny consisted of 51 sequences from 41 species. LDOX sequences from grape, tobacco, apple, kiwifruit and blueberry were also included in this analysis because of their high similarity in sequence and function of LDOX and ANS (Jun et al, 2018;Lafferty et al, 2022a). There were 62 sequences from 52 species included in the UFGT phylogenetic tree.…”
Section: Gene Identification and Phylogenetic Analysismentioning
confidence: 99%
“…More importantly, VcMYBPA1.1 gene expression profiles show peaks during early and late stages of development, when proanthocyanidins (PA) biosynthesis occurs and anthocyanins accumulate, respectively [ 42 ]. Furthermore, VcMYBA1 and VcMYBPA1 positively co-regulate the accumulations of PAs and anthocyanins by activating VcbHLH2 and VcMYBC2.1 [ 43 , 47 , 54 ]. The protein sequences of VcMYBA1 and VcMYBPA1 were highly homology to VcMYB437 and VcMYB336, respectively, in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, VcMYBA and VcMYB1 have been proved as important roles correlated with the expression of anthocyanin accumulation related structural gene, meanwhile they are able to transactivate the DFR promoter in blueberry fruit [ 1 , 14 ]. Differently, MYBC2.1 and MYBR3.1, activated by MYBPA1, are demonstrated as two distinct MYB repressors of both PA and anthocyanin biosynthesis [ 43 ]. Nonetheless, in order to understand how the R2R3-MYB regulators are involved in anthocyanin biosynthesis, a comprehensive functional characterization is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The colour change accompanied by anthocyanin accumulation is a critical process for the quality formation of blueberry fruit, making it an ideal material for studying fruit colouration (Zifkin et al ., 2012 ). While several transcriptional regulators and phytohormones have been documented to be implicated in regulating anthocyanin biosynthesis in blueberry fruit, knowledge regarding the regulatory network underlying the entire process of colour change is still limited (Farneti et al ., 2022 ; Jaakola et al ., 2010 ; Karppinen et al ., 2021 ; Lafferty et al ., 2022a , b ; Wang et al ., 2022b ; Xie et al ., 2022 ; Zifkin et al ., 2012 ). In a previous study, we demonstrated that VcMIR156a can influence anthocyanin and chlorophyll accumulation through its direct target VcSPL12 in tomato and Arabidopsis (Li et al ., 2020b ).…”
Section: Introductionmentioning
confidence: 99%